PENGARUH ETIKA, PERILAKU, DAN KEPRIBADIAN TERHADAP INTEGRITAS GURU - Sri Sarjana; Nur Khayati (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2016)
Integrity is one of requirements for teachers as a professional educator. Teachers with integrity is a role model for students. Strengthening teachers’ integrity is part of government policy to improving teacher quality in the future. The purpose of this study was to determine the effect of teachers’ ethics on teachers’ personality, the effect of teachers’ behavior on teachers’ personality, and the effect of teacher's personality on teachers’ integrity. This quantitative research developed explanatory survey method and the sample was 154 senior secondary school teachers in Bekasi district. Test of statistical data analysis using Structural Equation Modeling (SEM) with 8.8 Lisrel program and using SPSS 22. The results of this study shows that ethic and behaviour of teachers have a positive influence on their personality and it affects their integrity. Ethics and behaviour of teachers have an important role in improving the integrity through the development of the personality of the teacher. Efforts of teachers in improving their integrity is an essential need and it can be implemented through improving their ethics, developing their behaviour, and promoting their better personality. ABSTRAKPendidik yang berintegritas menjadi persyaratan bagi guru sebagai tenaga pendidik yang profesional. Guru yang berintegritas menjadi teladan dan contoh yang baik bagi siswa. Perlunya penguatan integritas guru menjadi bagian penting dari kebijakan pemerintah untuk pengembangan kualitas guru di masa depan. Penelitian ini bertujuan mengkaji pengaruh etika guru terhadap kepribadian guru, pengaruh perilaku guru terhadap kepribadian guru, dan pengaruh kepribadian guru terhadap integritas guru. Data didapatkan dari 154 guru SMA negeri di Kabupaten Bekasi. Jenis penelitian adalah penelitian kuantitatif yang mengembangkan metode explanatory survey. Uji analisis data statistik menggunakan Structural Equation Modeling (SEM) dengan program Lisrel 8.8 serta menggunakan SPSS 22. Hasil penelitian ini menujukkan bahwa etika dan perilaku guru memiliki pengaruh positif terhadap kepribadian dan berdampak terhadap integritas guru. Etika dan perilaku guru memiliki peran penting dalam meningkatkan integritas melalui pengembangan kepribadian guru. Kontribusi guru dalam meningkatkan nilai integritas sangat diperlukan melalui upaya memperbaiki etika, mengembangkan perilaku, dan mengedepankan kepribadian yang lebih baik.